(untitled) (Eureka Journal of Business, Economics & Innovation Studies, 2026)
The rapid development of artificial intelligence (AI) within the digital economy has transformed production processes, service delivery, and innovation systems worldwide. This study examines the impact of AI adoption on economic growth, labor productivity, and structural transformation. Using an extended production function framework that incorporates AI as a technological input, the analysis demonstrates that higher levels of AI integration are positively associated with total factor productivity and GDP growth. The findings indicate that AI enhances labor efficiency, promotes sectoral modernization, and stimulates innovation. At the same time, the study highlights potential challenges, including skill-biased technological change, labor market adjustments, and digital divides. The results provide theoretical and practical insights for policymakers aiming to maximize the benefits of AI while mitigating social and economic risks.